A Model for Evaluating the Impacts of Qualitative Characteristics on the Usefulness of Financial Reporting - Halimeh Rahmani; Hosein Jabari (International Journal of Management, Accounting and Economics, 2015)
The objective of accounting is to provide useful information for the users of financial reporting. The information is considered useful if it possess qualitative characteristics. In this regard, it is very important to examine the relationship between qualitative characteristics and usefulness of information. However, a literature review doesn’t contribute much to judge about the relationship between qualitative characteristics and the usefulness of financial reporting. This study aims to investigate the effects of qualitative characteristics on the usefulness of financial reporting. In this study, we have used structural equations model (SEM) to analyze the data. The PLS, LISREL and SPSS software were used to test the model, research validity and research reliability, respectively. The information of the study sample consisting of 185 firms was analyzed during the period 2000 to 2013. Except for understandability, all other qualitative characteristics had an impact on usefulness. Conservatism also had negative effect on usefulness. Based on the findings, it is recommended to omit conservatism from qualitative characteristics. Besides, considering that relevance has a greater impact on the usefulness than reliability, so it can be concluded that the users of financial statements are looking for relevant information in their decision making process and information reliability is a matter of secondary importance.